REPOSITIONING DIGITAL SOVEREIGNTY AS A CONSTITUTIONAL RIGHT: A CRITIQUE OF THE LIMITATIONS OF PERSONAL DATA PROTECTION IN THE ERA OF ARTIFICIAL INTELLIGENCE - M. Ferdiansyah Kholil (Qaumiyyah: Jurnal Hukum Tata Negara, 2026)
The advancement of Artificial Intelligence has transformed the landscape of personal data protection due to the ability of algorithms to generate inferred data and conduct profiling that extends beyond the original purpose of data collection. This situation challenges the effectiveness of data protection regimes that still rely on "notice and consent" mechanisms, as stipulated in Law Number 27 of 2022 concerning Personal Data Protection. Although various studies have addressed personal data protection and Artificial Intelligence governance, research framing digital sovereignty as a constitutional right in response to the limitations of the Personal Data Protection Law remains relatively limited. This study aims to analyze the limitations of personal data protection under the Personal Data Protection Law in the era of Artificial Intelligence and to reposition the concept of digital sovereignty as part of citizens' constitutional rights. The study employed a normative legal research method, utilizing both statutory and conceptual approaches. The results indicated that consent-based data protection mechanisms are currently unable to address the processing of inferential data generated by Artificial Intelligence systems, particularly those operating via "black box" algorithmic models. The findings offered a conceptual contribution by repositioning digital sovereignty as a constitutional right rooted in the protection of personal privacy and human dignity, as guaranteed under Article 28G paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Consequently, personal data protection in the Artificial Intelligence era must be understood not merely as an administrative issue of data management, but also as an integral part of protecting citizens' constitutional rights within the digital space. Abstrak Perkembangan Artificial Intelligence telah mengubah lanskap perlindungan data pribadi melalui kemampuan algoritma untuk menghasilkan data turunan (inferred data) dan melakukan profilasi yang melampaui tujuan awal pengumpulan data. Kondisi ini menimbulkan tantangan terhadap efektivitas rezim perlindungan data yang masih bertumpu pada mekanisme persetujuan pengguna (notice and consent), sebagaimana diatur dalam Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi. Meskipun berbagai penelitian telah membahas perlindungan data pribadi dan tata kelola Artificial Intelligence, kajian yang menempatkan kedaulatan digital sebagai hak konstitusional dalam merespons keterbatasan Undang-Undang Perlindungan Data Pribadi masih relatif terbatas. Penelitian ini bertujuan untuk menganalisis keterbatasan perlindungan data pribadi dalam ndang-Undang Perlindungan Data Pribadi di era Artificial Intelligence serta mereposisi konsep kedaulatan digital sebagai bagian dari hak konstitusional warga negara. Penelitian menggunakan metode hukum normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa mekanisme perlindungan data yang berbasis persetujuan belum mampu menjangkau pemrosesan data inferensial yang dihasilkan oleh sistem Artificial Intelligence, terutama yang beroperasi melalui model algoritmik Black Box. Temuan penelitian ini menawarkan kontribusi konseptual berupa reposisi kedaulatan digital sebagai hak konstitusional yang berakar pada perlindungan diri pribadi dan martabat manusia sebagaimana dijamin dalam Pasal 28G ayat (1) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Dengan demikian, perlindungan data pribadi di era Artificial Intelligence perlu dipahami tidak hanya sebagai isu administratif dalam pengelolaan data, tetapi juga sebagai bagian dari perlindungan hak konstitusional warga negara di ruang digital.